Childhood Trauma and Gender Attitudes Among Rural Left‐Behind Adolescents in China: A Latent Profile Analysis. - Zheng, Junyao; Zhou, Yiyan; Yang, Fan; Li, Wenjie; Liu, Shaowei (Child & Family Social Work, 2026)
Gender attitudes significantly shape adolescent development outcomes, yet their association with childhood trauma remains unclear, particularly among vulnerable populations. This study explored the relationship between childhood trauma and gender attitudes among rural left‐behind adolescents (LBA) in China, addressing a critical gap in understanding. The research surveyed 1258 LBA aged 12–17 in Hunan Province, utilizing the Attitudes towards Women Scale for Adolescents and the Childhood Trauma Questionnaire. Latent profile analysis identified three distinct trauma profiles: low neglect and abuse (69.5%), high neglect with low abuse (23.8%) and high neglect and abuse (6.8%). Regression analysis, controlling for sociodemographic variables, revealed significant associations between these profiles and gender attitudes. The profile with low neglect and abuse reported more egalitarian gender attitudes compared to the other profiles. While girls were more likely to fall into the high neglect, low abuse category, no significant gender differences were found in how trauma profiles related to overall gender attitudes. This study provides valuable insights into the complex interplay between childhood trauma and gender attitudes among LBA, highlighting the need for targeted interventions addressing child maltreatment, promoting egalitarian gender norms and empowering vulnerable youth.